Patterns of 'leakage' in the utilisation of clinical guidelines: A systematic review - Mickan, S; Burls, A; Glasziou, P (2011)
Background Research evidence is insufficient to change physicians' behaviour. In 1996, Pathman developed a four step model: that physicians need to be aware of, agree with, adopt, and adhere to guidelines. Objective To review evidence in different settings on the patterns of 'leakage' in the utilisation of clinical guidelines using Pathman's awareness-to-adherence model. Methods A systematic review was conducted in June 2010. Primary studies were included if they reported on rates of awareness and agreement and adoption and/or adherence. Results 11 primary studies were identified, reporting on 29 recommendations. Descriptive analyses of patterns and causes of leakage were tabulated and graphed. Leakage was progressive across all four steps. Median adherence from all recommendations was 34%, suggesting that potential benefits for patients from health research may be lost. There was considerable variation across different types of guidelines. Recommendations for drug interventions, vaccination and health promotion activities showed high rates of awareness. Leakage was most pronounced between adoption and adherence for drug recommendations and between awareness and agreement for medical management recommendations. Barriers were reported differentially for all steps of the model. Conclusion Leakage from research publication to guideline utilisation occurs in a wide variety of clinical settings and at all steps of the awareness-to-adherence pathway. This review confirms that clinical guidelines are insufficient to implement research and suggests there may be different factors influencing clinicians at each step of this pathway. Recommendations to improve guideline adherence need to be tailored to each step.